(untitled) (Applied Biological Research, 2016)
Interspecific hybrid between Gossypium hirsutum (AADD) cv. F 1861 and G. armourianum (DD) Acc. PAU 1 was generated and characterized along with parents at morphological and molecular levels. Female parent (F 1861) had erect growth habit, cream petals, palmate leaves, green stem, cream anthers, hairy stem and leaves; whereas male parent (PAU 1) had spreading growth habit, yellow petals, cordate leaves, reddish green stem, yellow anthers and glabrous plant body. The growth habit, petal colour, leaf shape and size of interspecific F1 hybrid were intermediate. Plant stem colour and hairiness, leaf pubescence and anther colour of G. armourianum Acc. PAU 1 were observed to be dominant as hybrid fully resembled Acc. PAU 1 for these characters. Petal spot was absent in F 1861 and present in PAU 1as well as hybrid. Variable expression of petal spot, anther colour and filament colour was observed in F1. The interspecific F1 hybrid was male-sterile. Significant differences were observed between the pollen size of parents as well as parents and their hybrid. Of the 33 SSR markers polymorphic between the parents, 8 markers unambiguously confirmed the hybrid status of interspecific hybrid. This hybrid may serve as a useful genetic resource